Dietary practices adopted by track-and-field athletes: Gluten-free, low FODMAP, vegetarian, and fasting - Lis, D. M.; Kings, D.; Larson-Meyer, D. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
A variety of special diets are adopted by track-and-field athletes for a multitude of reasons. Gluten-free (GFD), vegetarian, and fasting diets are among the more prevalent diets adopted for health, ethical, religious, and performance purposes. A low fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) diet is also gaining popularity as a beneficial strategy to reduce commonly occurring exercise-associated gastrointestinal symptoms (Costa et al., 2017). Due to the risks associated with unnecessary dietary restriction, special diets or dietary restraint should be carefully evaluated (Mountjoy et al., 2018). The following review will discuss the current state of knowledge, potential implications of select special diets, and practical considerations for implementation of these for track-and-field athletes aiming to optimize nutrition for health and performance.